From EHR to PHR: Let’s get the UK record straight - Symons,J; Ashrafian,H; Dunscombe,R; Darzi,A (BMJ Open, 2019)
This article reflects on the changing nature of health information access and the transition of focus from electronic health records (EHRs) to personal health records (PHRs) along with the challenges and need for alignment of national initiatives for EHR and PHR in the National Health Service (NHS) of the United Kingdom (UK).The importance of implementing integrated EHRs as a route to enhance the quality of health delivery has been increasingly understood. EHRs however carry several limitations that include major fragmentation through multiple providers and protocols throughout the NHS. Questions over ownership and control of data further complicate the potential for fully utilising records. Analysing the previous initiatives and the current landscape, we identify that adopting a patient health record system can empower patients and allow better harmonisation of clinical data at a national level. We propose regional PHR “hubs” to provide a universal interface that integrates digital heath data at a regional level with further integration at a national level.We propose that these PHR “hubs” will reduce the complexity of connections, decrease governance challenges and interoperability issues while also providing a safe platform for high-quality scalable and sustainable digital solutions, including artificial intelligence (AI) across the UK NHS, serving as an exemplar for other countries which wish to realise the full value of healthcare records.